Triaxial closed-loop measurement based on a single-beam zero-field optically pumped magnetometer - Wang, Kun; Zhang, Kaixuan; Zhou, Binquan; Lu, Fei; Zhang, Shaowen; Yan, Yeguang; Wang, Weiyi; Lu, Jixi (Frontiers in Physics, 2022)
In this study, we propose an approach for the simultaneous measurement of triaxial magnetic fields using a single-beam zero-field optically pumped atomic magnetometer, in which a rotational high-frequency (ω1) and another high-frequency (ω2) modulated magnetic field magnetic fields are applied along the transverse directions and the longitudinal direction, respectively. Theoretical analysis, numerical simulation, and experiments are conducted to demonstrate this method. Experimental sensitivities of 18 fT/Hz1/2 along the two transverse directions and 140 fT/Hz1/2 along the longitudinal direction are simultaneously achieved. On this basis, we operate the magnetometer in closed-loop mode to expand the bandwidth and dynamic range, and to keep the triaxial magnetic field sensed by the magnetometer at zero. The triaxial bandwidths are increased from below 100 Hz to over 1.6 kHz. The triaxial dynamic ranges are all extended to ±150 nT. Plus, we verify the ±1000 nT dynamic range of the triaxial magnetometer through increasing the triaxial coil constants. The synchronization of triaxial closed-loop measurement, simplicity of magnetometer structure, and closed-loop detection with high sensitivities make it applicable and attractive for biomagnetism imaging in challenging environments.